Perception of symptoms is out of proportion to cardiac pathology in patients with "diastolic heart failure". Issue 6 (10th December 2007) - Ingle, L; Cleland, J G F; Clark, A L
Abstract : Background: Epidemiological studies suggest that "diastolic heart failure" (DHF) is common and has a prognosis similar to that of systolic heart failure (SHF). We wanted to assess whether patients with breathlessness who were being treated for DHF had objective evidence of cardiac impairment and exercise limitation. Methods: Consecutive patients with a clinical diagnosis of chronic heart failure completed a standardised 6-minute walk test (6-MWT) and underwent an echocardiographic examination to determine the presence of major structural heart disease (MSHD). N-terminal pro-brain natriuretic peptide (NT-proBNP) was measured to determine degree of cardiac pathology. Results: 568 patients were identified with SHF (75.7% males) and 104 with DHF (54.7% males). They were compared with 400 healthy controls (matched with DHF group for age, sex and body mass index (BMI)). Controls (median (interquartile range); 43 (20–62) pmol/l)) and DHF patients (27 (13–67) pmol/l) had significantly lower NT-proBNP levels compared to SHF patients (178 (82–422) pmol/l). There was no difference in NT-proBNP levels between controls and DHF patients (p = 0.348). There was no correlation between BMI and NT-proBNP in either DHF (r 2 = 0.03; p = 0.287) or SHF (r 2 = 0.02; p = 0.346) patients. Both SHF and DHF patients reported similar degrees of breathlessness. 6-MWT distance (p = 0.973) was similar between SHF and DHF patients. DHF patients had a higher BMI (p<0.0001). Conclusion: Patients being treated for a clinical diagnosis of DHF have the same self-reported symptoms and 6-MWT performance as patients with SHF, yet have normal NT-proBNP levels. Their perception of their symptoms is out of proportion to their evidence of cardiac pathology.